Differential Analysis of Luxury Brand Extension Strategies in Different Cultural Contexts - Zhou, Chengxin (Transactions on Economics, Business and Management Research, 2024)
With the acceleration of globalization and the increasingly fierce competition in the market, luxury brands are facing many challenges in the process of seeking sustainable growth. As an important strategic tool, brand extension strategy is of great significance to the growth and development of luxury brands. Nevertheless, there are differences in consumers' perception and acceptance of luxury brands under different cultural backgrounds, which makes it necessary for luxury brands to consider the influence of cultural factors when implementing extension strategies. This paper emphasizes the importance of cultural sensitivity in luxury brand extension strategies. Firstly, this paper explains the definition and importance of luxury brand extension strategies, and through comparing the cases of luxury brand extension strategies in different cultural contexts, the paper provides references for luxury brands to formulate extension strategies that are more in line with their target markets, so as to enhance their brand value and market competitiveness.